HUBUNGAN PEMERINTAH PUSAT DAN PEMERINTAH DESA DALAM PELAPORAN KEUANGAN DESA - Alan Bayu Aji; Retno Agus Setiawan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
This article aims to determine the relationship between the central government and the village government in village financial reporting which is reviewed in a normative juridical manner through a statutory approach. Currently, the village government has a heavy burden because in addition to having to provide services directly to the community, it must make village financial reports both to the regional government and the central government. Based on these problems, this article has several formulations including (1) How to regulate the relationship between the central government and village governments in village financial reporting; and (2) How to Model the Relationship between the Central Government and the Village Government in the future in village financial reporting. This article is an article with a normative juridical type with a statutory approach and a conceptual approach. The relationship between the Central Government and the Village Government has occurred directly since the birth of the Village Law, the Village Government has an extra burden because it has to carry out all forms of instructions or rules made by the Central Government, especially in terms of Village Financial Reporting, so that the relationship between the Central Government and the Village Government seems formal and rigid, this can be seen from the various rules and policies from the central government that must be implemented by the village government, especially in the field of village financial reporting. There needs to be an arrangement that places more emphasis on the recognition of the village substantially through empowering the village government, and a simpler village financial reporting system through facilitation with an integrated village financial accountability reporting system.